MENJELAJAHI DIMENSI ESOTERIS PENDIDIKAN ISLAM MELALUI MOTIVASI KHIDMAH SANTRI: MENJELAJAHI DIMENSI ESOTERIS PENDIDIKAN ISLAM MELALUI MOTIVASI KHIDMAH SANTRI - Agus Riwanda; Mukhammad Zamzami; Abdullah Hosseinieskandian (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
This research investigates the significance of khidmah, or service, in the Islamic boarding school tradition as a means of gaining access to the esoteric components of Islamic education, particularly blessings. The motivation, process, and service orientation of musaidin students (serving students) at the Darullughah Wadda'wah Islamic Boarding School are the topic of this study. This qualitative study included 26 Musaidin students as participants, with data collected through in-depth interviews. The analysis was carried out by reducing, coding, and establishing themes. According to the findings of this study, the importance of loyalty to teachers and conformity with the norms of Islamic boarding schools carried out by Santri Musaidin in order to receive blessings. Santri Musaidin's compliance has an impact on positive behavior change, better living situations, economic well-being, and social acceptance. The experience of Santri Musaidin has transformed Islamic education not only in terms of greater knowledge, but also in terms of moral and spiritual growth.